Perceived organizational support and embeddedness as key mechanisms connecting socialization tactics to commitment and turnover among new employees - Allen, David G.; Shanock, Linda Rhoades (Journal of organizational behavior, 2013)
Retention of new hires is a critical issue for organizations. We propose that relationships are important mechanisms through which socialization tactics influence commitment and turnover. The key theoretical mechanisms connecting socialization tactics to turnover in our model are the extent to which newcomers perceive their relationship with the organization as supportive, caring, and entailing positive social exchanges and the extent to which newcomers become embedded within the organization. We collected longitudinal data from over 500 employees over the first year of employment. Consistent with our hypotheses, socialization tactics influence perceived organizational support (POS) and job embeddedness, and POS and embeddedness both relate to organizational commitment and voluntary turnover. Results support POS and embeddedness as relational mechanisms that bind employees to the organization as a result of socialization tactics.